Picture-based crop insurance: Is it feasible? Using farmers’ smartphone pictures to minimize the costs of loss verification - Kramer, Berber; Ceballos, Francisco; Hufkens, Koen; Melaas, Eli; Mishra, Azad; Mann, Michael L.; Toor, Mann S.; Robles, Miguel (International Food Policy Research Institute, 2017)
The Picture-Based Crop Insurance (PBI) project aims to develop a new way of delivering affordable and easy-to-understand crop insurance using farmers’ smartphone pictures to minimize the costs of loss verification. The project, funded by the CGIAR Research Program on Policies, Institutions, and Markets (PIM), is a partnership between the International Food Policy Research Institute (IFPRI), the Borlaug Institute for South Asia (BISA), HDFC Ergo General Insur-ance, Limited, and researchers from The George Washington Uni-versity, Boston University, and Ghent University.